2017
DOI: 10.1039/c7nr01214d
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast pressure sensing with transient tunnelling currents

Abstract: We report and systematically study large amplitude piezoresistance spikes in thin composite films under stress. These spikes are characterized by a unique double exponential decay which we demonstrate to be the signature of transient tunnelling currents. We establish an expression that predicts the dynamic conductivity of the composite with only three material parameters and use it to infer the magnitude of applied stress from resistance spikes, thus achieving quasi-instantaneous readout unhindered by viscoela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Firstly the dependence of the d.c. conductivity on HOPG filling fraction suggests that tunneling is the interparticle conduction mechanism. The composite conductivity was found to depart from the universal power law, G ∼ (ν − ν c ) α , as the critical conductivity exponent increases from 2 to 4.7 when the HOPG filling fraction increases from 24% to 32% [16]. Grimaldi and Balberg [5] have theoretically shown that this behavior may be ascribed to percolation through an extended network of nanoparticles electrically connected to one another through quantum tunneling.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Firstly the dependence of the d.c. conductivity on HOPG filling fraction suggests that tunneling is the interparticle conduction mechanism. The composite conductivity was found to depart from the universal power law, G ∼ (ν − ν c ) α , as the critical conductivity exponent increases from 2 to 4.7 when the HOPG filling fraction increases from 24% to 32% [16]. Grimaldi and Balberg [5] have theoretically shown that this behavior may be ascribed to percolation through an extended network of nanoparticles electrically connected to one another through quantum tunneling.…”
Section: Methodsmentioning
confidence: 99%
“…Our choice of model is drawn from observations of the resistance of composites subjected to stress cycles [16] and sequences of stress steps [17,18]. The stress protocols applied to composites of graphitic nanoparticles (HOPG) in polydimethylsiloxane (PDMS) are detailed by Chauhan et al [16]. In this section, we recall the remarkable features of these experiments which our theory will describe.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations